Jute and Jute Products of Bangladesh: Contributions and Challenges - Akter, Swapna; Sadekin, Md Nazmus; Islam, Nazrul (Asian Business Review, 2020)
Jute is one of Bangladesh’s main cash crops. The contribution of the jute sector to the economy of Bangladesh is enormous. In Bangladesh, Jute is a vital sector from economical, agricultural, industrial, and commercial perspectives. Different kinds of jute products are made in Bangladesh and the products are environmentally friendly as well. Every year Bangladesh earns an amount of foreign currency by exporting jute and jute products in different countries all over the world. That contributes to the national income of Bangladesh. Jute was once called Bangladesh's 'Golden Fibre. But this industry's present and future prosperity and growth are vulnerable. There exist many problems in the jute industry of Bangladesh, such as; lack of scientific knowledge and modern tools, market tools, unavailability of quality seeds, low productivity, inappropriate market forecasting, land fragmentation, natural calamities, conflicts and economic crisis in the world market, etc. Based on the existing problems, we will try to give some policies that may help to eradicate the problems and improve the present conditions of the jute industry in Bangladesh.